Blood Serum Stimulates p38-Mediated Proliferation and Changes in Global Gene Expression of Adult Human Cardiac Stem Cells - Höving, Anna L. (Cells, 2020)
During aging, senescent cells accumulate in various tissues accompanied by decreased regenerative capacities of quiescent stem cells, resulting in deteriorated organ function and overall degeneration. In this regard, the adult human heart with a generally low regenerative potential is of extreme interest as a target for rejuvenating strategies with blood borne factors that might be able to activate endogenous stem cell populations. Here, we investigated for the first time the effects of human blood plasma and serum on adult human cardiac stem cells (hCSCs) and showed significantly increased proliferation capacities and metabolism accompanied by a significant decrease of senescent cells, demonstrating a beneficial serum-mediated effect that seemed to be independent of age and sex. However, RNA-seq analysis of serum-treated hCSCs revealed profound effects on gene expression depending on the age and sex of the plasma donor. We further successfully identified key pathways that are affected by serum treatment with p38-MAPK playing a regulatory role in protection from senescence and in the promotion of proliferation in a serum-dependent manner. Inhibition of p38-MAPK resulted in a decline of these serum-mediated beneficial effects on hCSCs in terms of decreased proliferation and accelerated senescence. In summary, we provide new insights in the regulatory networks behind serum-mediated protective effects on adult human cardiac stem cells.